Strong Convergence Theorem for Multiple Sets Split Feasibility Problems in Banach Spaces. (2nd August 2016) - Shehu, Yekini
ABSTRACT: The purpose of this article is to study the iterative approximation of solution to multiple sets split feasibility problems in p -uniformly convex real Banach spaces that are also uniformly smooth. We propose an iterative algorithm for solving multiple sets split feasibility problems and prove a strong convergence theorem of the sequence generated by our algorithm under some appropriate conditions in p -uniformly convex real Banach spaces that are also uniformly smooth.